STRATEGI PENGEMBANGAN KAWASAN BUDIDAYA RUMPUT LAUT SEBAGAI WISATA KONSERVASI DAN EDUKASI BERBASIS MASYARAKAT DI PANTAI PANDAWA - I Made Trisna Semara; Ni Made Ayu Natih Widhiarini; Ni Nengah Ariastini; Ni Luh Sri Mandari (Jurnal Ilmiah Hospitality Management, 2017)
Seaweed cultivation in Pandawa Beach is one of the leading commodities of fishery that is still occupied by coastal communities. However, along with the development of tourism in Pandawa Beach, it resulted in some seaweed farmers switch professions into food and beverages traders, and tenants of tourism services and facilities. This phenomenon resulted in the decreasing of seaweed yields even it was not re-produced. Therefore, it needs a strategy of seaweed cultivation area development as conservation and educational tour in order to preserve the continuity of seaweed cultivation and the sustainability of tourism development; therefore it can improve the prosperity of the community. The purposes of this research were 1) to identify of internal and external potential of seaweed cultivation area as conservation tourism and community-based education in Pandawa Beach, 2) to design the development strategy of seaweed cultivation area as conservation tourism and community based education. The data was obtained from participants’ observation, questionnaire, and in-depth interviews with six informants consisting of seaweed farmers, cultivation group managers and managers of Pandawa Coastal Tourist Object as primary data, and documentation study as secondary data. Data collection techniques used were in-depth interviews, participatory observation, and documentation studies. Data analysis techniques used were qualitative descriptive analysis techniques, IFAS - EFAS, and SWOT. The findings of this research were 1) Seaweed Cultivation Area in Pandawa Beach had internal and external potential that is useful to be developed into conservation and education tourism based on community, 2) Seaweed cultivation development strategy as conservation tourism and community-based education in Pandawa Beach can be done by making educational tourism attractions, optimizing community-based management system, and optimizing marketing in the development of seaweed cultivation area as conservation tourism and community-based education in Pandawa Beach.